Accuracy and ease-of-use of seven point-of-care SARS-CoV-2 antigen-detecting tests: a multi-centre clinical evaluation - Krüger, Lisa; Tanuri, Amilcar; Lindner, Andreas K.; Gaeddert, Mary; Köppel, Lisa; Tobian, Frank; Brümmer, Lukas E.; Klein, Julian; Lainati, Federica; Schnitzler, Paul; Nikolai, Olga; Mockenhaupt, Frank P.; et al. (EBioMedicine, 2022)
Background - Antigen-detecting rapid diagnostic tests (Ag-RDTs) for SARS-CoV-2 are important diagnostic tools. We assessed clinical performance and ease-of-use of seven Ag-RDTs in a prospective, manufacturer-independent, multi-centre cross-sectional diagnostic accuracy study to inform global decision makers. - Methods - Unvaccinated participants suspected of a first SARS-CoV-2 infection were recruited at six sites (Germany, Brazil). Ag-RDTs were evaluated sequentially, with collection of paired swabs for routine reverse transcription polymerase chain reaction (RT-PCR) testing and Ag-RDT testing. Performance was compared to RT-PCR overall and in sub-group analyses (viral load, symptoms, symptoms duration). To understandusability a System Usability Scale (SUS) questionnaire and ease-of-use (EoU) assessment were performed. - Findings - 7471 participants were included in the analysis. Sensitivities across Ag-RDTs ranged from 70·4%-90·1%, specificities were above 97·2% for all Ag-RDTs but one (93·1%).Ag-RDTs, Mologic, Bionote, Standard Q, showed diagnostic accuracy in line with WHO targets (> 80% sensitivity, > 97% specificity). All tests showed high sensitivity in the first three days after symptom onset (≥87·1%) and in individuals with viral loads≥ 6 log10SARS-CoV2 RNA copies/mL (≥ 88·7%). Usability varied, with Rapigen, Bionote and Standard Q reaching very good scores; 90, 88 and 84/100, respectively. - Interpretation - Variability in test performance is partially explained by variable viral loads in population evaluated over the course of the pandemic. All Ag-RDTs reach high sensitivity early in the disease and in individuals with high viral loads, supporting their role in identifying transmission relevant infections. For easy-to-use tests, performance shown will likely be maintained in routine implementation. - Funding - Ministry of Science, Research and Arts, State of Baden-Wuerttemberg, Germany, internal funds from Heidelberg University Hospital, University Hospital Charité − Universitätsmedizin Berlin, UK Department of International Development, WHO, Unitaid.
Published online 24 December 2021
Gesehen am 28.06.2022